Inflammatory bowel disease: quality of life and influence of supplementation - Leitão, Mariana (2019)
Intestinal Inflammatory Disease includes Crohn's Disease and Ulcerative Colitis, which are chronic evolution diseases. The main symptoms of these diseases are diarrhea, abdominal pain, fever, and nausea which affect patients' quality of life. However, there is evidence that supplementation can help patients with the symptoms and improve quality of life.